Studi Perbandingan Kinerja Penggilingan Padi (Rice Milling Unit) Dengan dan Tanpa Pengering Buatan Berbahan Bakar Sekam di Kabupaten Tabanan - DIAN WIDY KUSUMAWATI; KETUT BUDI SUSRUSA; A.A.A WULANDIRA SUDIRAJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2012)
ABSTRACT A Comparison Study of Rice Milling Unit Performance With and Without Artificial Drying of Rice Husk Fuel in Tabanan Regency Post-harvest handling of rice is a strategic effort in maintaining the quality of rice in the process of drying and milling. Grain drying process can be performed with and without artificial drying. Artificial drying husk-fired technology is a breakthrough, because the husk is a source of bioenergy alternatives that can produce thermal energy for drying grain. The research was conducted in Tabanan in the District Highways Penebel, taken (purposive). In this study there were two attempts made in rice mills with drying rice husk-fueled and two census taken in the rice milling business without artificial drying was taken as (purposive). The data collected were analyzed quantitatively and qualitatively. The results showed that the use of artificial dryers influential and instrumental in increasing the volume of dry grain harvests, especially in the wet season. Comparisions between the employers perception of the rice milling quality of rice produced in court with and without artificial drying produced quality rice that are equally good. While the MH to generate artificial drying of rice quality is better than without artificial drying. Comparasion of profit per ton of grain in the rice milling business with smaller artificial drying of Rp. 259.716,81 than without artificial drying of Rp. 279.699,91. Need the addition of artificial dryers to increase the volume of unhusked rice yields and quality, especially in the wet season. In the rice milling business with artificial drying to increase profits, then the court should not use artificial drying or drying floor just use it. Further research needs to be done about the financial performance of the rice milling business with and without artificial drying. Keywords: performance of rice milling, drying grain, husk fuel